Transient inhibition of the posterior parietal cortex affects action-related but not action-unrelated visual processing during path integration - Bublatzky, Florian; Riemer, Martin (Journal of cognitive neuroscience, 2025)
Path integration refers to the ability to monitor self-motion cues to keep track of changes in position and orientation. This function is often assumed to rely predominantly on medial temporal lobe structures containing grid, place, and head direction cells. Recent evidence, however, suggests that key navigational computations may occur outside this system, for example, in posterior parietal areas. Here, we adopted a novel perspective derived from animal research and examined whether human path integration relies on processing streams in the posterior parietal cortex (PPC), depending on the involvement of actively controlled motion as opposed to passive perception of visual optic flow. We compared the effects of inhibiting the PPC via TMS on two path integration tasks in a virtual reality, only one of which involved active control of a visually simulated forward movement. Behavioral performance showed that distance judgments were selectively affected in the action-related path integration task. This finding shows that the processing of actively controlled motion depends on computations in the PPC, whereas passive processing of optic flow is largely independent of the PPC computations. Our results reinforce the hypothesis that the PPC plays a critical role for the integration of goal locations and self-positional signals within an egocentric frame of reference. In addition to the medial temporal lobe, the posterior parietal system is recruited during tasks involving actively controlled movements, whereas medial temporal computations are sufficient for passive monitoring of positional changes.